PENEGAKAN KODE ETIK DAN KODE PERILAKU KPK OLEH DEWAN PENGAWAS KPK - Bello, Petrus (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The many ethical violations by KPK personnel recently indicate that the level of compliance of KPK personnel towards KPK's code of ethics and code of conduct is weak and surely this raises the question of whether the KPK Supervisory Board has properly enforced KPK's code of ethics and conduct. This paper attempts to analyze the position of the KPK Supervisory Board and its role in enforcing KPK's code of ethics and conduct towards KPK Leaders and Employees. In analyzing the position of the KPK Supervisory Board, it will first be traced through Law Number 30 of 2002 concerning the Corruption Eradication Commission as last amended by Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission, and then traced through the Constitutional Court Decision Number 71/PUU-XVII/2019 dated May 4, 2021. This analysis is in order to strengthen the position of KPK Supervisory Board in enforcing KPK's code of ethics and conduct. This paper also attempts to propose a diagnosis of KPK's code of ethics and conduct on the one hand and the enforcement of KPK's code of ethics and conduct as well as the examination and implementation of trials for violations of that code of ethics and conduct committed by KPK personnel in order to realize the enforcement of KPK's code of ethics and conduct that is good and just.